1996
DOI: 10.1002/(sici)1097-4652(199606)167:3<500::aid-jcp14>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C mediates up-regulation of urokinase and its receptor in the migrating keratinocytes of wounded cultures, but urokinase is not required for movement across a substratum in vitro

Abstract: Both in cell culture and in vivo, keratinocytes that are migrating in response to a wound express enhanced levels of both urokinase-type plasminogen activator (uPA) and the uPA cell surface receptor (uPA-R). To explore the mechanism of this up-regulation, keratinocyte cultures were treated proir to wounding with a variety of metabolic and growth factor inhibitors in order to evaluate their effect on uPA and uPA-R expression. Actinomycin D and cycloheximide inhibited the up-regulation of both uPA and uPA-R, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 75 publications
(72 reference statements)
3
24
0
Order By: Relevance
“…It is not known which isotype of PKC is involved in the PKC-dependent migration, because GF109203X at the concentration used in the present study (5 M) attenuates the PKC activation of various subfamilies found in keratinocytes (24,25). Activation of PKC has been reported to play an important role in keratinocyte migration through enhancement of the specific integrin-mediated mo- tility (26), microfilament organization (27), or up-regulation of proteinases such as metalloproteinases (28) and urokinase (29). Requirement of PI3K activation for the Stat3-independent PKC-dependent signaling pathway toward migration was clearly demonstrated by in vitro studies by using wortmannin, a specific inhibitor of PI3K (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…It is not known which isotype of PKC is involved in the PKC-dependent migration, because GF109203X at the concentration used in the present study (5 M) attenuates the PKC activation of various subfamilies found in keratinocytes (24,25). Activation of PKC has been reported to play an important role in keratinocyte migration through enhancement of the specific integrin-mediated mo- tility (26), microfilament organization (27), or up-regulation of proteinases such as metalloproteinases (28) and urokinase (29). Requirement of PI3K activation for the Stat3-independent PKC-dependent signaling pathway toward migration was clearly demonstrated by in vitro studies by using wortmannin, a specific inhibitor of PI3K (Fig.…”
Section: Discussionmentioning
confidence: 86%
“…Although both keratinocytes and endothelial cells express increased levels of uPA and PAI-1 in response to monolayer wounding, uPA is apparently not required for keratinocyte locomotion in vitro, whereas occupancy of uPAR by uPA, but not uPA catalytic activity, facilitates wound-responsive endothelial 278 PROVIDENCE ET AL. cell motility (Pepper et al, 1987;Sato and Rifkin, 1988;Okedon et al, 1992;Ando and Jensen, 1996). Present data indicate that PAI-1 expression is an early response to injury and necessary for normal rat kidney-derived epithelial cells to effectively repair monolayer wounds.…”
Section: Discussionmentioning
confidence: 60%
“…In vitro migration into scrape-denuded areas is accomplished by the lateral movement of surviving cells across relatively uncomplicated substrates (e.g., Pepper et al, 1987;Sato and Rifkin, 1988;Ando and Jensen, 1996) unlike in vivo transit through fibrin-rich barriers or a provisional wound matrix Yamada and Clark, 1995). Despite these considerable physiologic differences, certain commonalites are evident between the two models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although altered mRNA stability and receptor recycling may be involved, the amounts of u-PAR are controlled mainly at the transcriptional level in malignancies such as colon cancer (Lund et al, 1995;Lengyel et al, 1996;Shetty et al, 1997;Gum et al, 1998). Altered transcription of the gene is the main mediator of u-PAR gene expression brought about by, for example, epidermal growth factor (EGF; Boyd, 1989), basic fibroblast growth factor (FGF; Mignatti et al, 1991), vascular endothelial growth factor (VEGF; Mandriota et al, 1995), transforming growth factor β type 1 (TGF-β1; Lund et al, 1995), phorbol 12-myristate 13-acetate (PMA; Lengyel et al, 1996), IFN-α or IFN-γ, (Wu et al, 2002), protein kinase C (PKC; Ando et al, 1996), protein kinase A (PKA)/c-AMP (Langer et al, 1993;Li et al, 1995), the MAPK- (Lengyel et al, 1997) and the JNK-pathway (Gum et al, 1998).…”
Section: Transcriptional Activation Of U-par Gene Expressionmentioning
confidence: 99%